2013
DOI: 10.1055/s-0033-1357119
|View full text |Cite
|
Sign up to set email alerts
|

Common Variants of the EPDR1 Gene and the Risk of Dupuytren's Disease

Abstract: The object of this study was the investigation of 3 common variants of single nucleotide polymorphisms of the ependymin-related gene 1 and its association with the occurrence of Dupuytren's disease. DNA samples were obtained from the peripheral blood of 508 consecutive patients. The control group comprised 515 healthy adults who were age-matched with the Dupuytren's patients. 3 common variants were analysed using TaqMan® genotyping assays and sequencing. The differences in the frequencies of variants of single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…[14][15][16][17][18] The function of EPDR1 is not well known, although several studies have reported its differential expression and single-nucleotide polymorphisms associated with its locus in different pathological and developmental processes, which are known to affect the cell adhesion. [19][20][21][22][23][24] Furthermore, genetic variants in EPDR1 have been reported to be linked to several diseases, including Dupuytren's disease 21,25,26 and primary angle closure glaucoma 23,27 ; however these observations do not provide obvious insight into the molecular functions of the protein. In 2016, Valiente et al reported that EPDR1 and its spliced isoforms are differentially expressed in human CRC cell lines, and the up-regulation of EPDR1 in human colorectal cancer was reported to promote cell growth, proliferation, and invasiveness.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18] The function of EPDR1 is not well known, although several studies have reported its differential expression and single-nucleotide polymorphisms associated with its locus in different pathological and developmental processes, which are known to affect the cell adhesion. [19][20][21][22][23][24] Furthermore, genetic variants in EPDR1 have been reported to be linked to several diseases, including Dupuytren's disease 21,25,26 and primary angle closure glaucoma 23,27 ; however these observations do not provide obvious insight into the molecular functions of the protein. In 2016, Valiente et al reported that EPDR1 and its spliced isoforms are differentially expressed in human CRC cell lines, and the up-regulation of EPDR1 in human colorectal cancer was reported to promote cell growth, proliferation, and invasiveness.…”
Section: Introductionmentioning
confidence: 99%
“…The function of EPDR1 is not well known, although several studies have reported its differential expression and single-nucleotide polymorphisms associated with its locus in different pathological and developmental processes, which are known to affect the cell adhesion [19][20][21][22][23][24]. Furthermore, genetic variants in EPDR1 have been reported to be linked to several diseases, including Dupuytren's disease [21,25,26] and primary angle closure glaucoma [23,27], however these observations do not provide obvious insight into the molecular functions of the protein. In 2016 F. Valiente et al reported that EPDR1 and its spliced isoforms are differentially expressed in human CRC cell lines, and the up-regulation of EPDR1 in human colorectal cancer was found to promote cell growth, proliferation, and invasiveness [28].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, there are metabolic abnormalities in the deposition of extracellular matrix proteins (especially collagen) and the presence of contractile myofibroblasts [ 13 ]. Genetic analysis of Dupuytren’s contracture revealed a marked elevation of ependymin-related protein 1 (EPDR1) gene expression [ 14 ], which reportedly contributes to excessive collagen contractility and fibroblast abnormalities [ 15 ].…”
Section: Introductionmentioning
confidence: 99%